An acetylenedicarboxylato-bridged Mn(ii)-based 1D coordination polymer: electrochemical CO2 reduction and magnetic properties. (13th March 2019) - Dutta, Basudeb; Maity, Suvendu; Ghosh, Soumen; Sinha, Chittaranjan; Mir, Mohammad Hedayetullah
Abstract : A Mn(ii )-based 1D coordination polymer, [Mn(adc)(4-phpy)2 (H2 O)2 ] n, (H2 adc = acetylenedicarboxylic acid and 4-phpy = 4-phenylpyridine) showed dual properties: electrochemical CO2 reduction and anti-ferromagnetism. Abstract : A new Mn(ii )-based one-dimensional coordination polymer (1D CP), [Mn(adc)(4-phpy)2 (H2 O)2 ] n, (1 ) (H2 adc = acetylenedicarboxylic acid and 4-phpy = 4-phenylpyridine) was synthesized using the linear dicarboxylate adc ligand. The structure of compound1 was obtained using the single-crystal X-ray diffraction (SCXRD) technique. Inspection of the solid-state structure revealed that compound1 formed a three-dimensional (3D) supramolecular aggregate using a combination of hydrogen bonding and C–H⋯π interactions. Interestingly, compound1 was found to behave as an efficient catalyst for the electrochemical reduction of CO2 . Variable-temperature magnetic measurements revealed the weak anti-ferromagnetic properties of compound1 .